Analisis Pengembangan Peningkatan Kompetensi Inovasi Aparatur Sipil Negara di Pemerintahan Daerah Kabupaten Poso - Inkiriwang, Verna Gladies Merry; Adnyani, Achintya Widhi; Suhariadi, Fendy (Universitas Islam Kadiri, 2025)
This study was conducted to analyze the development efforts to enhance innovation competence among Civil Servants (ASN) in the Local Government of Poso Regency. The main problem identified was the low implementation of innovation in task execution and public service, despite the availability of capacity-building programs. This study employed a qualitative approach using interviews, observations, and document analysis. The findings indicated that the improvement of innovation competence was influenced by relevant training availability, organizational work culture, supportive leadership, and individual motivation. However, several obstacles were found, including limited budget, lack of program sustainability, and insufficient innovation performance evaluation. This study concluded that innovation competence development must be structured, continuous, and integrated with the civil servant career development system in order to achieve adaptive and high-quality public services.